Analisis Hukum Kepler Dalam Gerak Planet Dan Satelit - Harefa, Faeri Destalenta; Halawa, Febrianus (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Kepler's laws are one of the most important milestones in the history of astronomy and physics, explaining the motion of planets and satellites around the sun. This research aims to analyse the existing literature on Kepler's Laws, including the First, Second and Third Laws of Motion. Through this analysis, it is expected to understand the contribution of Kepler's Laws to the development of science and technology, as well as their application in modern astronomy. The method used in this research is descriptive analysis of various relevant literature sources. The results show that Kepler's Law not only explains planetary motion, but also provides the basis for the development of Newton's theory of gravity and modern astronomy. In addition, the application of Kepler's Law in satellite technology and space missions demonstrates the relevance of this law in today's scientific and practical context.